Kajian Alat Tangkap Mini Trawl Nelayan Pulau Tinggi Desa Penutuk Kecamatan Lepar Pongok Kabupaten Bangka Selatan - Alias Pikal; Kurniawan Kurniawan; M Bachtiyar (Universitas Bangka Belitung, 2019)
Mini trawls are included in the classification of trawls with using the method of operation by means of being pulled by a moving ship chasing a group of fish. This research was conducted in February 2019 to March 2019 at Pulau Tinggi of Lepar Pongok South Bangka. The purpose of this research is to know fishing ground distribution of catching fish, indetification of fishing tools of mini trawl, identification the result of fishing catch and aspects of fishermen economic conditions of mini trawl. The method was used interview survey. The analysis was carried out by descriptive analysis. The result show that the location of fishing ground is 2 location that are Karang Pelawang waters and Pasir Putih Waters. The Identification of fishing tools of mini trawls there are wing of nets, belly, otter board, cod end, head rope, ground rope, warp rope, float and sinker. There are 8 spesies fish caught, the local name are Jerebung shrimp (Fenneropeanus merguienis), Selar fish (Selar crumenophtahalmus), Kurisi fish (Nemipterus furcosus), Pepetek (Leiognathus equulus), Cermin fish (Alectis indica), kuda laut (Hippocampus cuvier) dan Buntal fish(Legochepalus fugu).